2019
DOI: 10.4236/jep.2019.1010072
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis of the Determinants of the Adoption of Water and Soil Conservation Techniques in Burkina Faso: Case of Cotton Producers in the Province of Bam

Abstract: Soil degradation is a major problem in the Sudano-Sahelian zone of Burkina Faso. To maintain or improve soil productivity levels and limit Water losses, especially with rainfall variability, adaptation strategies have been developed that focus on water and Soil Conservation techniques (WSC). Although their agronomic benefits have been proven, adoption rates for these techniques are generally low, particularly among cotton farmers in Bam province. The main objective of this study is to identify the socioeconomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“… Mathieu et al (2019) applied a probit model to analyze the factors that determine the adoption of water conservation techniques among Bam cotton producers, the authors concluded that early warning, group membership, smartphone ownership, and cotton income are decisive factors. However, technical assistance and access to the pesticide were negative factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“… Mathieu et al (2019) applied a probit model to analyze the factors that determine the adoption of water conservation techniques among Bam cotton producers, the authors concluded that early warning, group membership, smartphone ownership, and cotton income are decisive factors. However, technical assistance and access to the pesticide were negative factors.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In fact, erosion has been noted as the largest widespread threat to the environment [1,2]. In particular, soil erosion causes 75 billion metric tons of soil to be displaced each year around the world [3]. Due to anthropogenic activities, rain events now pose an increased risk of irreparable soil erosion.…”
Section: Introductionmentioning
confidence: 99%
“…Some severely eroded soils are not useable for further crop production. Mathieu et al (2019) reported that approximately 75 billion metric tons of soil is removed annually from arable lands by wind and water, and around 80% of the world's land suitable for cultivation is moderately or severely eroded (Pimentel, 2006). According to Wuepper et al (2019), global average soil erosion rate reached 2.4 t ha -1 yr -1 .…”
Section: Introductionmentioning
confidence: 99%